Cultural identity and political ethics - Gilbert, Paul, 1942- (Edinburgh : Edinburgh University Press, 2010)
'Today, people's cultural identities are increasingly invoked in support of political claims, and these claims commonly lead to acrimony and violence. But what is'cultural identity', and what is its political significance? This book offers a provocatively sceptical answer to these questions. Tracing the idea back to the now largely discredited notion of national character, it argues that cultural identity is no deep going feature of individual psychology. Nor is it any uniform phenomenon. Rather, various types of so-called cultural identity emerge in response to the different circumstances people face. Such identities are marked by merely surface features of behaviour and these have a principally aesthetic appeal. In consequence, it is argued, cultural identities lack the ethical significance claimed for them and their invocation is in many ways politically pernicious.' -- Back cover
The politics of identity -- National character -- The idea of deep identity -- Types of identity -- The embodiment of cultural identity -- Identity and subjectivity -- The art of identity -- The ethics of identity
Includes bibliographical references and index
Keywords: Group identity -- Political aspects; Political sociology; Political ethics